Extraction and Application of Fruit Waste (Citrus Maxima) in Microalgae Harvesting - Ho, Agnes Yin Yee (Universiti Teknologi PETRONAS, 2017)
Harvesting microalgae has been increasingly relevant due to its potential as a biofuel source. Apparently, the coagulation-flocculation method is known as the most effective and convenient microalgae harvesting technique. However, human health and environmental concerns aroused when the inorganic coagulants are being excessively used in the conventional coagulation-flocculation process. Subsequently, the natural coagulants have emerged as an alternative to alleviate the problem. This proposed research specifically study the application of biopolymer (pectin) extracts from Citrus Maxima (pomelo)’s peel by hot sulphuric acid and ethanol precipitation in microalgae harvesting. Nevertheless, only the flavedo (green) of the pomelo skin is being used in the extraction process. After that, some physico-chemical properties of the extracted pectin were tested such as zeta potential and functional groups. The biopolymer is found negatively-charged and hence act as a coagulant aid in reducing sole dependency on inorganic coagulant.